PERANCANGAN LABORATORIUM CAMPURAN PERKERASAN HRS-WC DENGAN CRUMB RUBBER SEBAGAI FILLER - , WAHYU PURNOMO, Dr. Ir. Latif Budi Suparma, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Bitumen All this time, filler that commonly used in bitumen mixture is stone dust which has high processing cost, hence it is necessary to substitute stone dust with recycled material. Crumb rubber chosen as a replacement for stone dust, because it has the transcendence of increasing asphalt mixture resistance to water, withstand heavy traffic loads, and more flexible. mixture used in Indonesia is generally a hot mixed with gap graded, defined as thin layer of asphalt concrete (lataston or Hot Rolled Sheet). The purpose of this research was to understand the influence of crumb rubber as a substitute for stone dust in HRS- WC mixture filler. This research was limited to laboratory research by referencing to Spesifikasi Umum 2010, SNI, British Standard, AASHTO and ASTM. Several tests were carried out, namely (1) Marshall test (the characteristics of the mixture), (2) Indirect Tensile Strength test, and (3) Cantabro test (to obtain weight loss due to wheel load simulation). Pre-testing was needed in order to determine the maximum percentage of crumb rubber in the mixture. Based on the results of pre-testing, crumb rubber as fine aggregate should not more than 15% from the total fine aggregate, while as filler the maximum percentage was 20%. In this research the percentage of crumb rubber used was 0 %, 5 %, 10 %, and 15 % of the mixture. Based on the Marshall test results, stability value of crumb rubber with 0%, 5%, 10%, and 15% percentage were 1257.34 kg, 1309.77 kg